Study about Nasal Antrostomy for the Treatment of an Infected Maxillary Periapical (Radicular) Cyst - M. S. Nalini; Balasubramanya Kumar; Sunil Shroff (Current Progress in Medicine and Medical Research Vol. 5, 2023)
This case report presents a successful surgical man- agement of large infected radicular cyst. Radicular cysts are the most common cysts of the jaws, with occurrence of 7 to 54% of all the cysts in permanent dentition, whereas radicular cysts of deciduous dentition are extremely rare due to the natural course of milk tooth exfoliation. A 44-year-old male patient reported to private clinic, with a chief complaint of slowly progressing swelling on the left side of the face of 4 to 5 years duration. Most of the times, radicular cysts resemble the preexisting chronic peri- apical periodontitis lesions radiographically. The surgical enucleation of the cyst was carried out under general anesthesia and strict asepsis through an intraoral approach. The extent of the lesion, nearby anatomical structures, evolution, origin, clinical characteristics of the lesion, cooperation, and systemic health of the patient may all influence the treatment option.